Mortality of workers in the British cotton industry in 1968-1984. - Hodgson, J T; Jones, R D (Scandinavian Journal of Work, Environment & Health, 1990)
The mortality of 3458 cotton industry workers originally enrolled in a study of respiratory symptoms in the period 1968-1970 was followed to the end of 1984. Both the total mortality and the mortality from respiratory disease were less than expected, and they both decreased as length of service increased. However, for the subjects who initially reported byssinotic symptoms, the mortality from respiratory disease was slightly raised overall, and it increased with length of service. These patterns of mortality indicate a survivor effect (ie, a tendency for those with respiratory weakness to leave the industry), together with a long-term effect reflected in respiratory mortality on the health of those workers susceptible to the effects of cotton dust. The mortality from lung cancer was lower than expected, and it decreased with length of service. This finding is consistent with other observations that exposure to cotton dust may reduce the risk of lung cancer.